Formative experiences mediated by modality distance education and its implications on university work - Duarte, Luciana Martinez (2021)
The Secretariat of Distance Education of the Federal University of Rio Grande (FURG) enabled two professional training courses with pedagogical and technological support through the Distance Education modality (DE), in order to qualify the work of Administrative Technicians in Education (ATE) who work in the administrative spaces of the Institution. Within this context, this qualitative research aimed to understand how the ATE relate the courses in distance education with their daily practice. The data were produced through a questionnaire and analyzed by the Collective Subject Discourse method and from the analysis was generated the discourse "relationship between the lived experience and daily work activities", which supported some reflections, demonstrating the contribution of this developed education from the University's distance education structure. The speech expressed by the speech denotes advantages attributed by the subjects to the formation through the DE. The results reinforce that this modality, as a strategy, is effective in fulfilling the institutional objective of providing qualified training to the technical staff, paving the way to boost the development and hone skills necessary for the performance of the ATE activities. In addition, the formative strategy strengthens DE within FURG.